High prevalence of rare FBLIM1 gene variants in an Italian cohort of patients with Chronic Non-bacterial Osteomyelitis (CNO) - Adamo Pio d'Adamo; Anna Monica Bianco; Giovanna Ferrara; Martina La Bianca; Antonella Insalaco; Alberto Tommasini; Manuela Pardeo; Marco Cattalini; Francesco La Torre; Martina Finetti; Clotilde Alizzi; Gabriele Simonini; et al. (BMC, 2020)
Abstract Background FBLIM1 gene has been recently demonstrated to be involved in the pathogenesis of bone sterile inflammation. The aim of the study is to evaluate the prevalence of FBLIM1 gene variants in a cohort of 80 Italian patients with Chronic Non-bacterial Osteomyelitis (CNO). Methods The coding regions of FBLIM1 gene were sequenced in a cohort of 80 patients with CNO using DNA extracted from blood lymphocytes, and PCR products were sequenced. Only rare (global MAF < 2%), coding variants detected were considered. Clinical evaluation of patients with rare variants and those without was performed. Fisher's exact test was used to compare categorical and ordinal data, and Student's t-test was used to analyze continuous data. Results Eighteen out of 80 patients (~ 22%) presented at least one rare coding variant in FBLIM1. Eight patients presented a variant never associated before with CNO. All patients presented classical features of CNO and no statistical difference between patients with presence of FBLMI1 variants and those without were found in terms of clinical manifestation, treatment, and outcome. Conclusion Considering the high frequency of rare variants in our CNO cohort, our data seem to confirm a possible role of FBLIM1 in the pathogenesis of CNO suggesting that CNO is a disorder of chronic inflammation and imbalanced bone remodeling.